GAMBARAN KADAR ALBUMINURIA PADA SUBJEK DIABETES MELITUS DENGAN DAN TANPA PENYAKIT JANTUNG KORONER - Cendra, Sandy; Moeis, Emma; Langi, Yuanita (e-CliniC, 2014)
Abstract: Albuminuria is a marker of the decline in renal physiology and function of endothelial. Endothelial dysfunction is an early pathogenesis of coronary heart disease (CHD). High coronary heart disease complications in patients with diabetes mellitus (DM). Objective To know the description and differences in levels of albuminuria in diabetic patients with and without CHD inpoli Metabolic and Endocrine and poli Heart BLU. RSU. Prof. dr. R. D Kandou Manado. Research Method: Cross Sectional descriptive analytic study conducted in patients with diabetes mellitus pieces with and without coronary heart disease in Poli Endocrine Metabolic and poli heart BLU. RSU. Prof. dr. R. D Kandou Manado period November 2012 - November 2013. Results: From 34 patients with diabetes mellitus found the number of diabetic patients with CHD were 17 patients and 17 patients for diabetes without CHD, which consisted of 14 male patients and 20 female patients. The distribution of the sample based on CHD and sex, showed that diabetic patients with CHD were 9 men (26.47%) and 8 women (23.53%). As for diabetic patients without CHD as many as 5 male patients (14.70%) and 12 female patients (35.30%). Distribution of the study sample by CHD and RAKU categories showed diabetic patients with CHD were 7 patients (20.59%) and normal RAKU 10 patients (29.41%) RAKU abnormal. As for diabetic patients without CHD by 16 patients (47.06%) and 1 patient RAKU normal (2.94%) RAKU abnormal. Conclusion: Albuminuria occurs more frequently in patients with diabetes mellitus with coronary heart disease than diabetes mellitus without coronary heart diseaseKeywords: Albuminuria, diabetes mellitus, coronary heart disease.    Abstrak: Albuminuria merupakan petanda terjadinya penurunan faal ginjal dan disfungsi endotel. Disfungsi endotel merupakan patogenesis awal penyakit jantung koroner (PJK). Komplikasi penyakit jantung koroner tinggi pada pasien diabetes melitus (DM). Tujuan: Untuk mengetahui gambaran dan perbedaan kadar albuminuria pada pasien DM dengan dan tanpa PJK di Poli Endokrin Metabolik dan Poli Jantung BLU. RSU. Prof. dr. R. D Kandou  Manado. Metode Penelitian: Dilakukan penelitian deskriptif analitik lintang potong pada penderita diabetes melitus dengan dan tanpa penyakit jantung koroner di Poli Endokrin Metabolik dan Poli Jantung BLU.RSU. Prof. dr. R. D Kandou  Manado periode November 2012 – November 2013. Hasil: Dari 34 pasien Diabetes Melitus ditemukan jumlah pasien DM dengan PJK sebanyak 17 pasien dan 17 pasien untuk DM tanpa PJK, yang terdiri atas 14 orang pasien laki-laki dan 20 pasien wanita. Distribusi sampel berdasarkan PJK dan jenis kelamin, didapatkan hasil pasien DM dengan PJK yaitu sebanyak 9 orang laki-laki (26,47 %) dan 8  orang perempuan (23,53%). Sedangkan untuk pasien DM tanpa PJK yaitu sebanyak 5 orang pasien laki-laki (14,70%) dan 12 orang pasien perempuan (35,30%). Distribusi sampel penelitian berdasarkan PJK dan RAKU Kategori didapatkan hasil pasien DM dengan PJK sebanyak 7 pasien (20,59%) RAKU normal dan 10 pasien (29,41%) RAKU abnormal. Sedangkan untuk pasien DM tanpa PJK sebanyak 16 pasien (47,06%) RAKU normal dan 1 pasien (2,94%) RAKU abnormal. Simpulan: Albuminuria lebih banyak terjadi pada pasien diabetes melitus dengan penyakit jantung koroner dibandingkan diabetes melitus tanpa penyakit jantung koroner Kata kunci: Albuminuria, diabetes melitus, penyakit jantung koroner.